Recombinant bacteriophage T4 Rnl1 impacts Streptococcus mutans biofilm formation. Issue 1 (1st January 2021) - Chen, Juxiu; Chen, Zhanyi; Yuan, Keyong; Huang, Zhengwei; Mao, Mengying
ABSTRACT: Bacteriophage T4 RNA ligase 1 (T4 Rnl1) can be stably expressed in many bacteria and has been reported to affect the bioactivity of the host bacteria. Recently, we constructed bacteriophage T4 Rnl1 expressing system in Streptococcus mutans, a crucial biofilm-forming and dental caries-causing oral pathogen. Here, we characterized the function of recombinant bacteriophage T4 Rnl1 in biofilm formation of S. mutans. The T4 Rnl1 mutant exhibited similar growth phenotype but resulted in a significant reduction of biofilm biomass compared to wild type strain and empty plasmid carrying strain. The abnormal biofilm of the T4 Rnl1 mutant harbored loose bacterial clusters with defective production and distribution of exopolysaccharides. Moreover, the expression of several biofilm formation-associated genes was dysregulated at mRNA level in the T4 Rnl1 mutant. These results reveal that the bacteriophage T4 Rnl1 exert antibiofilm activities against the cariogenic bacterium S. mutans, which impacts the spatial organization of the exopolysaccharides and further impairs the three-dimensional biofilm architecture. These findings implicate that manipulation of bacteriophage T4 Rnl1, a biological tool used for RNA ligation, will provide a promising approach to cariogenic biofilm control.